Investigation on the Analgesic and Anti-inflammatory Effects of Curcumin in Mice - M Kavousi; S Kazemi; M Hashemi; AA Mohgadamnia (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2016)
BACKGROUND AND OBJECTIVE: Curcumin is the main ingredient of turmeric which has been used in traditional medicine for pain relief. This study was done to investigate the mechanism of possible analgesic and anti-inflammatory effect of curcumin using hot-plate and formalin method on mice.